1981
DOI: 10.1136/bmj.283.6302.1300
|View full text |Cite
|
Sign up to set email alerts
|

How is gastroenteritis treated?

Abstract: corner of the heater with her face applied closely to the grill. She was immediately immersed under the cold-water tap of a bath, and medical help was sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Eighty (7%) children were below the third centile for weight. One 12 (1) 5 (<1) 1052 fathers were employed. Ninety three families (8%) had established social worker involvement and 101 (9%) were first or second generation immigrants.…”
Section: Resultsmentioning
confidence: 99%
“…Eighty (7%) children were below the third centile for weight. One 12 (1) 5 (<1) 1052 fathers were employed. Ninety three families (8%) had established social worker involvement and 101 (9%) were first or second generation immigrants.…”
Section: Resultsmentioning
confidence: 99%
“…. a European (if not obviously Irish) tone re-emerges on Into the Music [1979], leading into the stunning cauldron of audacious experiment represented by the vocal performances on Common One [1980] . .…”
Section: Placing Van Morrison's Voicementioning
confidence: 99%
“…Studies in other industrialized countries have shown that while the prevalence of antiemetic prescribing decreased, antiemetics continued to be prescribed for 4.5% to 19% of children admitted to the hospital with AGE. [23][24][25][26][27][28] The only US-based study looking at this issue revealed that a significant proportion of children younger than 6 years were prescribed promethazine therapy (an antiemetic)-14% of hospitalized children and 3.8% of all children with AGE. 29 However, that study was conducted in a single staff model health maintainence organization with a history of successfully deploying clinical practice guidelines, so the findings of Christakis et al 29 may not be generalizable to children cared for in other settings.…”
Section: Commentsmentioning
confidence: 99%